How to catch a turkey ebook - Wallace, Adam (How to Catch., 2018)
A New York Times Bestseller! From the bestselling How to Catch series comes a festive turkey tale and Thanksgiving book for kids! A turkey is running loose in a school right before a Thanksgiving play. Can YOU help catch it so the show can go on? Follow along as students turn their school upside down trying to catch the turkey, ending with a twist that ensures no turkeys are harmed (or eaten!). This hilariously zany children's picture book combines STEAM concepts and traps with a silly story and fun illustrations, perfect for starting a new fall family tradition this autumn or giving as a Thanksgiving gift for kids ages 4 and up! Thanksgiving time is here again, but there's a turkey on the run! Can you catch this tricky bird before the school play has begun? Also in the How to Catch Series: How to Catch a Unicorn How to Catch the Easter Bunny How to Catch an Elf How to Catch a Monster How to Catch a Leprechaun and more!